Further tales of Uncle Remus : the misadventures of Brer Rabbit, Brer Fox, Brer Wolf, the Doodang, and other creatures - Lester, Julius. 1939-2018 (Dial Books, 1990)
A retelling of the classic Afro-American tales relating the adventures and misadventures of Brer Rabbit and his friends and enemies.